2016
DOI: 10.1002/cphc.201501080
|View full text |Cite
|
Sign up to set email alerts
|

Steric Effects Govern the Photoactivation of Phytochromes

Abstract: Phytochromes constitute a superfamily of photoreceptor proteins existing in two forms that absorb red (Pr) and far-red (Pfr) light. Although it is well-known that the conversion of Pr into Pfr (the biologically active form) is triggered by a ZE photoisomerization of the linear tetrapyrrole chromophore, direct evidence is scarce as to why this reaction always occurs at the methine bridge between pyrrole rings C and D. Here, we present hybrid quantum mechanics/molecular mechanics calculations based on a high-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…In the phy and opsin proteins, isomerization produces similar effects, strengthening the hypothesis that Δ V 1 > 0 reflects mainly steric and geometric rearrangements. Recently, quantum mechanics/molecular mechanics calculations on Deinococcus radiodurans BphP ( Dr BphP) have shown that steric effects are indeed a key factor in determining isomerization selectivity and efficiency, when the bilin chromophore is embedded within the protein . In Sy Cph1‐R, two different D‐ring geometries exists, one of which is thought to be planar (silent) and the second has a pretwisted C15 = C16 double bond induced by HB to H290 (active); as a consequence of pretwisting, the latter has a much higher Φ I = 0.29 ( vs 0.03 for the former) .…”
Section: Discussionmentioning
confidence: 99%
“…In the phy and opsin proteins, isomerization produces similar effects, strengthening the hypothesis that Δ V 1 > 0 reflects mainly steric and geometric rearrangements. Recently, quantum mechanics/molecular mechanics calculations on Deinococcus radiodurans BphP ( Dr BphP) have shown that steric effects are indeed a key factor in determining isomerization selectivity and efficiency, when the bilin chromophore is embedded within the protein . In Sy Cph1‐R, two different D‐ring geometries exists, one of which is thought to be planar (silent) and the second has a pretwisted C15 = C16 double bond induced by HB to H290 (active); as a consequence of pretwisting, the latter has a much higher Φ I = 0.29 ( vs 0.03 for the former) .…”
Section: Discussionmentioning
confidence: 99%
“…Building on the same benchmark study, the QM region included the BV chromophore and the side chain of Cys24 to which it is linked. Recently, this scheme has also been used to explain why the most favorable double‐bond photoisomerization of BV in Dr BphP is the one occurring at C15−C16 …”
Section: Figurementioning
confidence: 99%
“…Recently, this scheme has also been used to explain why the most favorable doublebond photoisomerization of BV in DrBphP is the one occurring at C15ÀC16. [33] First, the structures of native DrBphP and of DrBphP with either of nitrogens A, B or C deprotonated (the latter three forms are henceforth denoted n A DrBphP, n B DrBphP and n C DrBphP; see Figure 2) were relaxed by performing geometry optimizations with the QM region described with the B3LYP functional. The procedure to consider only potential-energy minimum structures of the different forms, instead of ensembles of structures sampled from classical molecular dynamics (MD) trajectories, has a three-fold rationale.…”
Section: Computational Identification Of Pyrrole Ring C As the Prefermentioning
confidence: 99%
“…The red pigment derived from organism is an important member in the family of dyestuff from biomass. Pyrrole structure microbial pigment, called prodigiosin, recently have become a research hotspot for its bright colors and antibacterial function [8,9]. This pigment was a kind of intracellular metabolite.…”
Section: Introductionmentioning
confidence: 99%